CONFLICT OF CONDUCT LOCAL GOVERNMENT AGENCIES IN THE CITY BAUBAU (Case Study Executive Institution with the Legislative Drafting Baubau City budget for Fiscal Year 2015) - Daeru, Harun; Nur, Suratman; Yunus, Muh.; *, Hasniati (IJRDO - Journal of Applied Management Science, 2015)
The purpose of this research is to explain the behavior of the conflict between the executive by the legislature at the discussion stage Public Policy Budget (KUA), the stage of discussion of priorities and Provisional Budget Ceiling (PPAS) and the stage of discussion of the Draft Budget and Expenditure (budgets) Government Baubau city as well as to analyze the model settlement of the conflict between the executive and the legislature in the discussion of the Regional Budget (APBD) Baubau town of Fiscal Year 2015. The experiment was conducted at the Government Baubau City with informants namely the executive, in this case the Government Baubau City and legislature namely legislators Baubau City. Analysis of data using qualitative analysis through data reduction, data presentation and verification. The study found that there was a disagreement and debate between the executive and legislative institutions that pose a conflict behavior in terms of determining the development theme of Baubau 2015, determining the development priorities of Baubau, determining the macro-economic framework regions, determine the basic assumptions used in the preparation of budgets , conflict in determining the policy of regional revenue, expenditure and financing conflict areas in the discussion stage KUA Government Baubau City fiscal year 2015. There is disagreement in determining income plan that is sourced from local revenue, prioritize programs and activities, determine shopping areas not directly and determine provisional budget ceilings for direct spending behaviors that cause conflict between the executive and the legislature in the discussion of priorities and Provisional Budget Ceiling (PPAS) Government Baubau fiscal City year 2015. The conflict and debate that lead to behavioral conflict between the executive and the legislature also occurs in the discussion the draft Budget (APBD) District Government Baubau fiscal year 2015. The exact model used in resolving the conflict between the executive and the legislature in the preparation of the Regional Budget (APBD) of Baubau namely "Model Settling Conflicts" which complements the model two-dimensional conflict suggested by Robbins in order to prevent the ongoing conflict.